Cartografía de saberes colonizados: los vacíos de ‘verdad’ - Medina, Gabriel (Revista Segurança Urbana e Juventude, 2009)
This essay is about the need to differ the traditions of the thoughts that feed knowledge produced in Latin America. It tries to understand that it is a differential movement in the western legacy, and that it bets that on epistemic relation with the socalled tradition.It searches to recognize the limits of the western legacy and of the false universals that has built them. The author is interested in presenting the few possibilities that the Latin American reflexion has in building realities while it is still submerged in the tradition of our host thoughts. Thus he assumes that the difference leads us to figure out a “locus de enunciación” in each other’s interlocution.